Celastrol Attenuates the Invasion and Migration and Augments the Anticancer Effects of Bortezomib in a Xenograft Mouse Model of Multiple Myeloma - Shanmugam, Muthu K.; Ahn, Kwang S.; Lee, Jong H.; Kannaiyan, Radhamani; Mustafa, Nurulhuda; Manu, Kanjoormana A.; Siveen, Kodappully S.; Sethi, Gautam; Chng, Wee J.; Kumar, Alan P. (Frontiers in Pharmacology, 2018)
Several lines of evidence have demonstrated that deregulated activation of NF-κB plays a pivotal role in the initiation and progression of a variety of cancers including multiple myeloma (MM). Therefore, novel molecules that can effectively suppress deregulated NF-κB upregulation can potentially reduce MM growth. In this study, the effect of celastrol (CSL) on patient derived CD138+ MM cell proliferation, apoptosis, cell invasion, and migration was investigated. In addition, we studied whether CSL can potentiate the apoptotic effect of bortezomib, a proteasome inhibitor in MM cells and in a xenograft mouse model. We found that CSL significantly reduced cell proliferation and enhanced apoptosis when used in combination with bortezomib and upregulated caspase-3 in these cells. CSL also inhibited invasion and migration of MM cells through the suppression of constitutive NF-κB activation and expression of downstream gene products such as CXCR4 and MMP-9. Moreover, CSL when administered either alone or in combination with bortezomib inhibited MM tumor growth and decreased serum IL-6 and TNF-α levels. Overall, our results suggest that CSL can abrogate MM growth both in vitro and in vivo and may serve as a useful pharmacological agent for the treatment of myeloma and other hematological malignancies.